Older adult and family caregiver preferences for emergency department based-palliative care: An experience-based co-design study - Rebecca Wright; Karen Lowton; Bryan R. Hansen; Patricia Grocott (Elsevier, 2021)
Background: Older adults (>65 years) with palliative care needs are increasingly accessing the emergency department. Some interventions have been developed to improve the care provided, but the majority of research has focused on provider perspectives. Limited understanding of patient and family experiences and priorities means important needs may be overlooked. Objectives: To explore patient and family caregiver experiences and identify their improvement priorities for emergency department-based palliative care delivery. Design: A participatory action research design, experienced-based co-design, was adopted. Filmed and audio-recorded interviews and individual feedback sessions were used to capture patient data. Setting: An urban emergency department in the UK. Participants: Six patients aged ≥65 with palliative care needs and four family caregivers were recruited from the emergency department. Methods: Participants took part in individual or dyad audio-recorded or filmed interviews. Interview data were analyzed using thematic framework analysis. One-to-one feedback sessions with participants were used to validate findings and rank the themes to identify patient and family priorities for improvement. Results: The analysis identified five prominent themes that captured the patient and family experience of emergency department-based palliative care. 1) Systems and processes; 2) communication and information; 3) changing expectations (of what can be done for one's health on a personal and system level); 4) recommendations (for improving palliative care in the emergency department); and, 5) acknowledgement and validation (of the patient and family). All themes except 'recommendations' were selected as improvement priorities. Within the context of these improvement priorities, participants provided rich insights into their perceptions of care and identified small but significant actions that could be implemented to improve their experiences of palliative care in the emergency department. These included being offered a drink or phone call, being included in conversations about their care, and being kept informed of what was happening with their care. Conclusions: Older people with palliative care needs and their family caregivers were able to share their experiences and highlight improvement priorities for emergency department care using the experience-based co-design approach. Their experiences offer new perspectives, which can be used alongside emergency department and palliative care clinician perspectives to support service and outcome measure development in future emergency department-based palliative care. Tweetable abstract: #EBCD study shows older adults with #PalliativeCare needs value communication, compassion & inclusion in #SharedDecisionMaking in the #ED